'ForCyt' DNA database of wildlife species. (December 2017) - Ahlers, N.; Creecy, J.; Frankham, G.; Johnson, R.N.; Kotze, A.; Linacre, A.; McEwing, R.; Mwale, M.; Rovie-Ryan, J.J.; Sitam, F.; Webster, L.M.I.
Abstract: Wildlife crime continues unabated contributing to the extinction or near extinction of many plant and animal species. Species identification is a key tool in the enforcement of national legislation. If no morphology exists, comparison of DNA sequences generated from a mitochondrial gene are compared to those on a reference database, commonly GenBank. Sequences up-loaded to GenBank are unregulated and can lead to uncertainty with the adequacy of this DNA sequence repository for identification in a forensic context. We propose the establishment of ForCyt as a fully-regulated database of species that are commonly encountered in forensic investigations. The establishment of ForCyt will allow confidence in future species identification; something that is an absolute requirement to ensure high quality forensic science.